Radiation damage of CsI and CsI:Tl crystals containing impurities of carbonate and hydroxide; 3rd International Congress on Radiation Physics and Chemistry of Condensed Matter, High Current Electronics and Modification of Materials with Particle Beams and Plasma Flows - Trefilova L. N. Larisa Nikolaevna; Yakovlev V. Yu. Viktor Yurjevich; Alekseev V. D. Vadim Dmitrievich; Мелешко А. А. Анна Алексеевна; Mitichkin A. I. (2012, 2012)
Title screen